Physician–Pharmacist Collaborative Management of Asthma in Primary Care. Issue 10 (20th August 2014) - Gums, Tyler H.; Carter, Barry L.; Milavetz, Gary; Buys, Lucinda; Rosenkrans, Kurt; Uribe, Liz; Coffey, Christopher; MacLaughlin, Eric J.; Young, Rodney B.; Ables, Adrienne Z.; Patel‐Shori, Nima; Wisniewski, Angela
<x xml:space="preserve">Abstract</x> Objective To determine if asthma control improves in patients who receive physician–pharmacist collaborative management (PPCM) during visits to primary care medical offices. Design Prospective pre–post study of patients who received the intervention in primary care offices for 9 months. The primary outcome was the sum of asthma‐related emergency department (ED) visits and hospitalizations at 9 months before, 9 months during, and 9 months after the intervention. Events were analyzed using linear mixed‐effects regression. Secondary analysis was conducted for patients with uncontrolled asthma (Asthma Control Test [ACT] less than 20). Additional secondary outcomes included the ACT, the Asthma Quality of Life Questionnaire by Marks (AQLQ‐M) scores, and medication changes. Intervention Pharmacists provided patients with an asthma self‐management plan and education and made pharmacotherapy recommendations to physicians when appropriate. Results Of 126 patients, the number of emergency department (ED) visits and/or hospitalizations decreased 30% during the intervention (p=0.052) and then returned to preenrollment levels after the intervention was discontinued (p=0.83). Secondary analysis of patients with uncontrolled asthma at baseline (ACT less than 20), showed 37 ED visits and hospitalizations before the intervention, 21 during the intervention, and 33 after the intervention was discontinued (p=0.019). ACT and AQLQ‐M scores improved during the intervention (ACT mean absolute increase of 2.11, AQLQ‐M mean absolute decrease of 4.86, p<0.0001) and sustained a stable effect after discontinuation of the intervention. Inhaled corticosteroid use increased during the intervention (p=0.024). Conclusions The PPCM care model reduced asthma‐related ED visits and hospitalizations and improved asthma control and quality of life. However, the primary outcome was not statistically significant for all patients. There was a significant reduction in ED visits and hospitalizations during the intervention for patients with uncontrolled asthma at baseline. Our findings support the need for further studies to investigate asthma outcomes achievable with the PPCM model.